Covalent chemistry on nanostructured substrates enables noninvasive quantification of gene rearrangements in circulating tumor cells - Dong, Jiantong (Sci Adv, 2019)
Well-preserved mRNA in circulating tumor cells (CTCs) offers an ideal material for conducting molecular profiling of tumors, thereby providing a noninvasive diagnostic solution for guiding treatment intervention and monitoring disease progression. However, it is technically challenging to purify CTCs while retaining high-quality mRNA.Here, we demonstrate a covalent chemistry–based nanostructured silicon substrate (“Click Chip”) for CTC purification that leverages bioorthogonal ligation–mediated CTC capture and disulfide cleavage–driven CTC release. This platform is ideal for CTC mRNA assays because of its efficient, specific, and rapid purification of pooled CTCs, enabling downstream molecular quantification using reverse transcription Droplet Digital polymerase chain reaction. Rearrangements of ALK/ROS1 were quantified using CTC mRNA and matched with those identified in biopsy specimens from 12 patients with late-stage non–small cell lung cancer. Moreover, CTC counts and copy numbers of ALK/ROS1 rearrangements could be used together for evaluating treatment responses and disease progression.